Caracterização do esteróide α-espinasterol como um novo antagonista do receptor TRPV1 com efeito antinociceptivo - Santos, Gabriela Trevisan dos (2011)
The transient receptor potential vanilloid 1 (TRPV1) is relevant to the perception of noxious information and has been studied as a therapeutic target for the development of new analgesics. The goal of this study was to perform in vivo and in vitro screens to identify novel, efficacious, and safe TRPV1 antagonists isolated from leaves of the medicinal plant Vernonia tweedieana Baker. All of the fractions and the hydroalcoholic extract produced antinociception in mice during the capsaicin test, but the dichloromethane fraction (Dcm) also had antioedematogenic effect. Among the compounds isolated from the Dcm fraction, only α-spinasterol reduced the nociception and oedema induced by capsaicin injection. Moreover, α-spinasterol demonstrated good oral absorption and high penetration into the brain and spinal cord of mice. Besides, α-spinasterol was able to displace [3H]-resiniferatoxin (RTX) binding and diminish calcium (Ca2+) influx mediated by capsaicin. Orally administration of the Dcm fraction and α-spinasterol also produced antinociceptive effect in the noxious heat-induced nociception test; however, they did not change the mechanical threshold of naive mice. The treatment with α-spinasterol did not produce antinociceptive effect in mice systemically pre-treated with RTX. In addition, α- spinasterol and the Dcm fraction also reduced the oedema, mechanical and heat hyperalgesia elicited by complete Freund s adjuvant (CFA) paw injection. The Dcm fraction and α-spinasterol did not affect body temperature or locomotor activity. In conclusion, α-spinasterol is an efficacious and safe antagonist of the TRPV1 receptor with antinociceptive effect.